Initial endosseous healing response to lactide/ glycolide copolymer - Dilcele Silva Moreira DZIEDZIC; Isabella Caroline BERTOJA; João César ZIELAK (Revista Sul-Brasileira de Odontologia, 2010)
Introduction: The search for less invasive treatments, with fast and effective bone regeneration, has lead to the development of synthetic bioresorbable alternatives for bone graft. The commercial product FisiograftTM gel (Ghimas Spa, Italy), based on lactide-glycolide copolymer, is used as an injectable biocompatible and bioresorbable material for filling bone defects in dental surgery applications. These polymers are also used in the production of suture threads, pins and plates for bone fixation, and barriers for guided tissue regeneration. Objective: The main objective of this pilot study was to observe the initial bone healing response after the application of polylactide-glycolide graft material in adult animals. Material and methods: Bone defects were prepared in right and left femora of 12 month-old male Wistar rats. The defects in one leg received the synthetic graft material and the contra-lateral defects did not receive any treatment. After four days, the animals were subjected to euthanasia, the femora were removed, and tissue blocks were prepared for histological analysis. Results: Blood clot remained in the centre of control defects with initial connective tissue organization on the edges. The graft material was observed in the centre of the treated defects, restricted to the area where it was applied, with neovascularization next to the graft material. The pattern of bone healing did not differ between groups, starting from the margins of the defects and from bone fragments, with neovascularization followed by deposition of non-mineralized bone matrix towards the centre. Conclusion: The results indicate that the lactide-glycolide copolymer gel was effective as a filling and osteoconductive material, allowing tissue healing during its resorption process. Additional studies are necessary to verify its capacity to promote bone regeneration.